Awareness on tetrodotoxin of illegal activity: forensic issue from a rare homicide case report and literature review. (April 2021) - Li, Juntao; Zhang, Xiangyu; Ye, Yi; Li, Xuewen; Gu, Yan; Yun, Libing
Abstract: The authors describe an extremely rare case of homicide by injecting tetrodotoxin (TTX) as lethal neurotoxin found in puffer fish. After a thorough investigation, the male victim was found to have a broken stalk from syringe needle in the subcutaneous tissue of left buttock and severe asphyxia confirmed by the main pathological findings at autopsy. During tortuous toxicological analysis，TTX was revealed by ultra high performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) as well as acute intoxication confirmed from forensic examination. The literature of qualitative and quantitative determination of TTX from human fluids was also reviewed to expect widely acceptable detection strategies. This case highlighted the importance of TTX toxicant with chemical formula name purchased through e-commerce，so as to improve particular emphasis and supervision on harmful substances possibly using hidden information or illegal means. Histopathological and toxicological results demonstrated here provided a reference and other useful information to the challenges of forensic casework. In general, the case report illustrates medico-legal issues of more attention to the possibility of TTX poisoning in rapid death and the need of routine postmortem tox screening in future practice. Highlights: An extremely rare case of homicide by injecting tetrodotoxin (TTX) as lethal neurotoxin found in puffer fish. TTX was revealed by UPLC-MS/MS as well as acute intoxication confirmed from forensic examination. TTX toxicant with chemical formula name purchased through e-commerce by illegal means reminds of forensic precaution.